Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1037/xlm0001113
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and stability of habit learning depend on temporal signal variation.

Abstract: The visual system can learn statistical regularities and form search habits that guide attention to a region where a target frequently appears. Although regularities in the real world can change over time, little is known about how such changes affect habit learning. Using a location probability learning task, we demonstrated that a constant target location probability resulted in a long-term habit-like attentional bias to the target-frequent location. However, when the target probability changed over time in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Active alteration of target templates during visual search affects the emergence of spatial bias, but it does not affect after the emergence of spatial bias 25 . While the present study showed an interference effect of featural inconsistency on spatial bias, previous studies have shown resistance of existing bias despite target template changes (i.e., item features, search difficulty 13 ).…”
Section: Discussionmentioning
confidence: 93%
“…Active alteration of target templates during visual search affects the emergence of spatial bias, but it does not affect after the emergence of spatial bias 25 . While the present study showed an interference effect of featural inconsistency on spatial bias, previous studies have shown resistance of existing bias despite target template changes (i.e., item features, search difficulty 13 ).…”
Section: Discussionmentioning
confidence: 93%